Aluminum conductive paste for solar cells and preparation method thereof

By adding silver-doped composite nanofibers and silver nanoparticles to the aluminum conductive paste to form a mesh structure to disperse heat stress, the problem of silicon wafer bending during the sintering and cooling process of aluminum conductive paste is solved, and the photoelectric conversion efficiency and yield of solar cells are improved.

CN115985548BActive Publication Date: 2025-03-18NINGBO RING ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211669591.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-03-18
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

In the prior art, thermal stress generated by aluminum conductive paste during sintering and cooling causes silicon wafers to bend, affecting the yield rate and photoelectric conversion efficiency of solar cells.

Method used

By adding silver-doped composite nanofibers to the aluminum conductive paste, a network structure is formed to disperse and transfer thermal stress, suppress the shrinkage and deformation of the aluminum back field, and improve the toughness and electrical conductivity of the composite nanofibers through silver nanoparticles modification.

Benefits of technology

It effectively reduces the curvature of the silicon wafer, improves the photoelectric conversion efficiency of solar cells, and improves the yield rate of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115985548B_ABST
    Figure CN115985548B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of solar cells, and in particular to an aluminum conductive paste for solar cells and a preparation method thereof, wherein the aluminum conductive paste comprises aluminum powder, silver-doped composite nanofibers, inorganic powders, organic additives, and metal element compounds. The aluminum conductive paste for solar cells provided in the present invention improves the paste formula and the paste preparation method, effectively disperses and transmits the thermal stress generated by the aluminum conductive paste during sintering and cooling, thereby inhibiting the shrinkage deformation of the aluminum back surface field and improving the stability of the aluminum back surface field size structure, thereby effectively reducing the curvature of silicon wafers and reducing the warping of silicon wafers. At the same time, it also helps to improve the photoelectric conversion efficiency of solar cells, thereby achieving the effect of improving the yield rate of solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cells, in particular to an aluminum conductive paste for solar cells and a preparation method thereof. Background Art

[0002] Crystalline silicon solar cells are semiconductor devices that convert light energy directly into electrical energy. They are the leading products in the current photovoltaic market, and conductor paste is the main auxiliary material for making crystalline silicon solar cells. Among them, aluminum conductive paste is a type of conductor paste. It is printed on the entire backlight surface of the battery and forms a PP+ junction, providing part of the open circuit voltage for the battery. Therefore, the performance of aluminum conductive paste has an important impact on the electrical performance of the battery.

[0003] In the current crystalline silicon solar cell manufacturing process, due to the difference in linear thermal expansion coefficients of aluminum and silicon, the aluminum back surface shrinks relatively more during sintering and cooling, while the size of the silicon wafer remains basically unchanged. Under the action of shrinkage stress, the silicon wafer will produce a certain degree of bending, which directly affects the yield of the solar cell and the subsequent assembly process. In the prior art, there is a method for preparing a back aluminum conductor slurry for crystalline silicon solar cells. Although the glass powder used in the technical solution has stable chemical properties and a low expansion coefficient, it can be applied to the aluminum conductor slurry to reduce the bending of the silicon wafer to a certain extent, but the effect is general. In addition, due to the general conductivity of the glass powder, adding it to the aluminum conductor slurry will also cause the conductivity of the solar cell to deteriorate, thereby resulting in unsatisfactory photoelectric conversion efficiency of the solar cell.

[0004] Since silicon is the main raw material of crystalline silicon solar cells, lighter and thinner silicon wafers are the future development trend, and thinner silicon wafers are more likely to bend. Therefore, it is very important to find a method that does not affect the photoelectric conversion efficiency of solar cells and can effectively reduce the curvature of silicon wafers. Summary of the invention

[0005] In view of the defects existing in the prior art, the present invention provides an aluminum conductive paste for solar cells and a preparation method thereof. By improving the paste formula and the paste preparation method, the thermal stress generated by the aluminum conductive paste during sintering and cooling is effectively dispersed and transferred, thereby suppressing the shrinkage deformation of the aluminum back surface field and improving the stability of the aluminum back surface field size structure, thereby effectively reducing the curvature of the silicon wafer and reducing the warping of the silicon wafer. At the same time, it also helps to improve the photoelectric conversion efficiency of the solar cell, thereby achieving the effect of improving the yield rate of the solar cell.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] Aluminum conductive paste for solar cells, comprising aluminum powder, silver-doped composite nanofibers, inorganic powder, organic additives, and metal element compounds; based on the total weight of the aluminum conductive paste, the content of the aluminum powder is 70-82wt%, the content of the composite nanofiber powder is 5-10wt%, the content of the inorganic powder is 1-3wt%, the content of the organic additive is 10-20wt%, and the content of the metal element compound is 0.1-0.6wt%.

[0008] As a further preferred embodiment of the present invention, the inorganic powder is at least one of zirconium tungstate and zirconium vanadate;

[0009] The metal element compound is at least one of tetraethyltin, dibutyltin dilaurate, tetrabutyl lead and silver laurate;

[0010] The organic auxiliary agent contains 5-12 wt% of a thickener, 1-5 wt% of a lubricant, 1-5 wt% of a thixotropic agent and 80-90 wt% of an organic solvent.

[0011] Furthermore, the organic solvent is selected from at least one of terpineol, turpentine, ethylene glycol ethyl ether acetate, and tributyl citrate.

[0012] As a further preferred embodiment of the present invention, the preparation method of the silver-doped composite nanofiber is as follows:

[0013] 1) dissolving an appropriate amount of polyacrylonitrile and polyvinyl pyrrolidone in N,N-dimethylformamide, stirring for 3-5 hours, adding zirconium n-propoxide and glacial acetic acid, mixing well to form a spinning solution for electrospinning, pre-oxidizing the obtained product in air for 1-3 hours, then keeping it warm in a nitrogen atmosphere for 1-2 hours, and cooling it to room temperature to obtain composite nanofibers;

[0014] 2) After the composite nanofibers are fully washed with anhydrous ethanol, they are immersed in a sufficient amount of nitric acid solution and soaked at room temperature for 3-5 hours. After being taken out, they are immersed in a sufficient amount of tin chloride aqueous solution and soaked at room temperature for 1-3 hours. After being taken out, they are placed in a mixed solution and transferred to a reactor. The reaction is carried out at 120-130° C. for 5-8 hours. After being taken out, they are repeatedly washed with distilled water and then dried.

[0015] Furthermore, in step 1), in the spinning solution, the ratio of polyacrylonitrile, polyvinyl pyrrolidone, N,N-dimethylformamide, zirconium n-propoxide and glacial acetic acid is (3-6) g: (4-9) g: (60-100) mL: (7-13) mL: (3-5) mL;

[0016] The electrospinning is carried out at a voltage of 11-15 kV and a spinning rate of 1.1-1.6 mL / h;

[0017] The pre-oxidation temperature is 255-280°C;

[0018] The insulation temperature is 1200-1300°C.

[0019] Furthermore, in step 2), the concentration of the nitric acid solution is 8-10 mol / L;

[0020] The concentration of the tin chloride aqueous solution is 13-18 g / L;

[0021] The mass volume ratio of the composite nanofiber to the mixed solution is 1: (30-50) g / mL;

[0022] The mixed solution consists of 0.12-0.18 g / mL glucose solution, 0.20-0.25 g / mL polyvinyl pyrrolidone solution, 15-20 wt % ammonia water and 20-30 g / L silver nitrate solution in a volume ratio of (3.6-4.5):1:(2.8-3.2):(4.0-4.6).

[0023] A method for preparing aluminum conductive paste for solar cells, the specific operations are as follows:

[0024] The silver-doped composite nanofibers are pretreated, crushed and ground to obtain powder, which is dispersed in an organic additive together with a metal element compound. After mixing, aluminum powder and inorganic powder are added and ground to obtain the aluminum conductive paste, wherein the fineness of the aluminum conductive paste is <20 μm and the viscosity is 30,000-40,000 Pa.s.

[0025] As a further preferred embodiment of the present invention, the pretreatment of the silver-doped composite nanofibers is specifically performed as follows:

[0026] 1) Weigh an appropriate amount of potassium antimony tartrate and dissolve it in deionized water, stir for 10-30 minutes, add polyvinyl pyrrolidone and continue stirring for 10-20 minutes after it is fully dissolved, then add thioacetamide to the mixed solution and continue stirring for 30-40 minutes to obtain a reaction solution for standby use;

[0027] 2) Adding the silver-doped composite nanofibers to the reaction solution, then transferring it to a reactor, sealing it and placing it in an oven for constant temperature reaction. After the reaction is completed, cooling it to room temperature, taking out the product, repeatedly rinsing it with deionized water, and drying it.

[0028] Furthermore, in step 1), in the reaction solution, the ratio of potassium antimony tartrate, deionized water, polyvinyl pyrrolidone, and thioacetamide is (7.2-8.9) g: (30-50) mL: (0.2-0.6) g: (2.3-2.7) g;

[0029] The stirring speed is 500-800r / min.

[0030] Furthermore, in step 2), the ratio of the silver-doped composite nanofibers to the reaction solution is 1: (10-30) g / mL;

[0031] The isothermal reaction temperature is 180-200° C., and the reaction time is 4-5 hours.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] In the present invention, the characteristics of carbon fiber with high electrical conductivity and chemical stability are utilized, polyacrylonitrile is used as a carbon source, and carbon nanofibers with high surface area, high electrical conductivity and high high temperature resistance are obtained by electrostatic spinning, and nanoparticles of metal oxide are doped into the carbon nanofibers to improve the toughness of the carbon nanofibers, thereby obtaining composite nanofibers with excellent mechanical properties. By adding the composite nanofibers into aluminum conductive paste, the composite nanofibers can be overlapped to form a mesh structure. The formed mesh structure has good toughness and can effectively disperse and transfer the thermal stress generated by the aluminum conductive paste during sintering and cooling, thereby effectively offsetting the thermal stress, eliminating the phenomenon of stress concentration near the mesh structure, thereby inhibiting the shrinkage deformation of the aluminum back surface field, and improving The stability of the aluminum back surface field size structure is improved, thereby effectively reducing the curvature of the silicon wafer and reducing the warping of the silicon wafer; at the same time, in order to repair some defects on the surface of the composite nanofibers, improve the structural integrity of the composite nanofibers, and make the composite nanofibers have more excellent mechanical properties, in the present invention, silver nanoparticles are used to modify the surface of the composite nanofibers, which can repair defects such as holes and cracks on the surface of the composite nanofibers, further improve the toughness of the composite nanofibers, thereby further reducing the curvature of the silicon wafer, and the surface modified silver nanoparticles help to improve the electrical conductivity and electrocatalytic activity of the composite nanofibers, thereby improving the photoelectric conversion efficiency of solar cells, so that the performance of solar cells is improved.

[0034] In order to improve the stability of the mesh structure formed by the overlap of silver-doped composite nanofibers in the aluminum conductive paste, in the present invention, potassium antimony tartrate and thioacetamide are used as antimony sources and sulfur sources, and antimony sulfide nanoparticles are deposited on the surface of the silver-doped composite nanofibers by a hydrothermal method. By controlling the reaction time, the antimony sulfide nanoparticles are agglomerated, and some mesh structures grow from the surface. This part of the mesh structure is used as a cross-linking node to increase the contact area between the silver-doped composite nanofibers, which is conducive to the overlap of the silver-doped composite nanofibers to form a stable mesh structure. At the same time, this part of the mesh structure evolved from antimony sulfide will also be entangled with each other, thereby constructing a multi-level and multi-dimensional mesh structure in the aluminum conductive paste, which can further offset the thermal stress generated by the aluminum conductive paste during sintering and cooling, inhibit the shrinkage deformation of the aluminum back field, and further reduce the curvature of the silicon wafer.

[0035] The aluminum conductive paste for solar cells provided by the present invention improves the paste formula and the paste preparation method, and effectively disperses and transfers the thermal stress generated by the aluminum conductive paste during sintering and cooling, thereby suppressing the shrinkage deformation of the aluminum back surface field and improving the stability of the aluminum back surface field size structure, thereby effectively reducing the curvature of the silicon wafer and reducing the warping of the silicon wafer. At the same time, it also helps to improve the photoelectric conversion efficiency of the solar cell, thereby achieving the effect of improving the yield rate of the solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0037] Figure 1 This is a graph showing the effect of silver-doped composite nanofiber content on the warpage of the battery cell. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] Aluminum conductive paste for solar cells, comprising aluminum powder, silver-doped composite nanofibers, zirconium tungstate, organic additives, and tetraethyl tin; based on the total weight of the aluminum conductive paste, the content of the aluminum powder is 70wt%, the content of the composite nanofiber powder is 5wt%, the content of the inorganic powder is 1wt%, the content of the organic additive is 23.9wt%, and the content of the metal element compound is 0.1wt%.

[0041] The organic auxiliary agent contains 10 wt % of ethyl cellulose, 5 wt % of hexadecanol, 5 wt % of polyamide wax powder and 80 wt % of pine alcohol.

[0042] The preparation method of silver-doped composite nanofibers is as follows:

[0043] 1) 3 g of polyacrylonitrile and 4 g of polyvinyl pyrrolidone were dissolved in 60 mL of N,N-dimethylformamide, stirred at 60 r / min for 3 h, and then 7 mL of zirconium n-propoxide and 3 mL of glacial acetic acid were added and mixed to form a spinning solution. Electrospinning was performed at a voltage of 11 kV and a spinning rate of 1.1 mL / h. The obtained product was pre-oxidized at 255° C. in air for 1 h, then kept at 1200° C. in a nitrogen atmosphere for 1 h, and cooled to room temperature to obtain composite nanofibers.

[0044] 2) After the composite nanofibers are fully washed with anhydrous ethanol, they are immersed in a sufficient amount of 8 mol / L nitric acid solution, immersed at room temperature for 3 hours, taken out and immersed in a sufficient amount of 13 g / L tin chloride aqueous solution, immersed at room temperature for 1 hour, taken out and placed in a mixed solution, the mass volume ratio of the composite nanofibers to the mixed solution is controlled to be 1:30 g / mL, the mixed solution is composed of 0.12 g / mL glucose solution, 0.20 g / mL polyvinyl pyrrolidone solution, 15 wt% ammonia water and 20 g / L silver nitrate solution in a volume ratio of 3.6:1:2.8:4, transferred to a reactor, reacted at 120°C for 5 hours, taken out and repeatedly washed with distilled water and then dried.

[0045] A method for preparing aluminum conductive paste for solar cells, the specific operations are as follows:

[0046] The silver-doped composite nanofibers are pretreated, crushed and ground to obtain powder, which is dispersed in an organic additive together with a metal element compound, mixed, and then aluminum powder and inorganic powder are added and ground to obtain the aluminum conductive paste, wherein the fineness of the aluminum conductive paste is <20 μm and the viscosity is 30,000 Pa.s.

[0047] The pretreatment of the silver-doped composite nanofibers is specifically performed as follows:

[0048] 1) Weigh 7.2 g of potassium antimony tartrate and dissolve it in 30 mL of deionized water, stir at 500 r / min for 10 min, and after it is fully dissolved, add 0.2 g of polyvinyl pyrrolidone and continue stirring for 10 min, then add 2.3 g of thioacetamide to the mixed solution and continue stirring for 30 min to obtain a reaction solution for standby use;

[0049] 2) Add silver-doped composite nanofibers to the reaction solution, control the ratio of the two to be 1:10 g / mL, then transfer to a reactor, seal it and place it in an oven, and react at a constant temperature of 180°C for 4 hours. After the reaction is completed, cool it to room temperature, take out the product, rinse it repeatedly with deionized water, and dry it.

[0050] Example 2

[0051] Aluminum conductive paste for solar cells, comprising aluminum powder, silver-doped composite nanofibers, zirconium tungstate, organic additives, and tetraethyl tin; based on the total weight of the aluminum conductive paste, the content of the aluminum powder is 73wt%, the content of the composite nanofiber powder is 7wt%, the content of the inorganic powder is 3wt%, the content of the organic additive is 16.5wt%, and the content of the metal element compound is 0.5wt%.

[0052] The organic auxiliary agent contains 10 wt % of ethyl cellulose, 2 wt % of hexadecanol, 3 wt % of polyamide wax powder and 85 wt % of pine alcohol.

[0053] The preparation method of silver-doped composite nanofibers is as follows:

[0054] 1) 5 g of polyacrylonitrile and 7 g of polyvinyl pyrrolidone were dissolved in 80 mL of N,N-dimethylformamide, stirred at 80 r / min for 4 h, and then 11 mL of zirconium n-propoxide and 4 mL of glacial acetic acid were added and mixed to form a spinning solution. Electrospinning was performed at a voltage of 13 kV and a spinning rate of 1.4 mL / h. The obtained product was pre-oxidized at 265 ° C in air for 2 h, then kept at 1250 ° C in a nitrogen atmosphere for 1.5 h, and cooled to room temperature to obtain composite nanofibers;

[0055] 2) After the composite nanofibers are fully washed with anhydrous ethanol, they are immersed in a sufficient amount of 9 mol / L nitric acid solution, immersed at room temperature for 4 hours, taken out and immersed in a sufficient amount of 15 g / L tin chloride aqueous solution, immersed at room temperature for 2 hours, taken out and placed in a mixed solution, the mass volume ratio of the composite nanofibers to the mixed solution is controlled to be 1:40 g / mL, the mixed solution is composed of 0.15 g / mL glucose solution, 0.23 g / mL polyvinyl pyrrolidone solution, 18 wt% ammonia water and 25 g / L silver nitrate solution in a volume ratio of 4.2:1:3:4.5, transferred to a reactor, reacted at 125°C for 6 hours, taken out and repeatedly washed with distilled water and then dried.

[0056] A method for preparing aluminum conductive paste for solar cells, the specific operations are as follows:

[0057] The silver-doped composite nanofibers are pretreated, crushed and ground to obtain powder, which is dispersed in an organic additive together with a metal element compound, mixed, and then aluminum powder and inorganic powder are added and ground to obtain the aluminum conductive paste, wherein the fineness of the aluminum conductive paste is <20 μm and the viscosity is 35000 Pa.s.

[0058] The pretreatment of the silver-doped composite nanofibers is specifically performed as follows:

[0059] 1) Weigh 8.3 g of potassium antimony tartrate and dissolve it in 42 mL of deionized water, stir at 700 r / min for 20 min, and after it is fully dissolved, add 0.5 g of polyvinyl pyrrolidone and continue stirring for 15 min, then add 2.5 g of thioacetamide to the mixed solution and continue stirring for 35 min to obtain a reaction solution for standby use;

[0060] 2) Add silver-doped composite nanofibers to the reaction solution, control the ratio of the two to be 1:20 g / mL, then transfer to a reactor, seal it and place it in an oven, and react at a constant temperature of 190°C for 4.5 hours. After the reaction is completed, cool it to room temperature, take out the product, rinse it repeatedly with deionized water, and dry it.

[0061] Example 3

[0062] Aluminum conductive paste for solar cells, comprising aluminum powder, silver-doped composite nanofibers, zirconium tungstate, organic additives, and tetraethyl tin; based on the total weight of the aluminum conductive paste, the content of the aluminum powder is 72wt%, the content of the composite nanofiber powder is 10wt%, the content of the inorganic powder is 2.4wt%, the content of the organic additive is 15wt%, and the content of the metal element compound is 0.6wt%.

[0063] The organic auxiliary agent contains 7wt% of ethyl cellulose, 3wt% of hexadecanol, 3wt% of polyamide wax powder and 87wt% of pine alcohol.

[0064] The preparation method of silver-doped composite nanofibers is as follows:

[0065] 1) 6 g of polyacrylonitrile and 9 g of polyvinyl pyrrolidone were dissolved in 100 mL of N,N-dimethylformamide, stirred at 100 r / min for 5 h, and then 13 mL of zirconium n-propoxide and 5 mL of glacial acetic acid were added and mixed to form a spinning solution. Electrospinning was performed at a voltage of 15 kV and a spinning rate of 1.6 mL / h. The obtained product was pre-oxidized at 280 ° C in air for 3 h, then kept at 1300 ° C in a nitrogen atmosphere for 2 h, and cooled to room temperature to obtain composite nanofibers;

[0066] 2) After the composite nanofibers are fully washed with anhydrous ethanol, they are immersed in a sufficient amount of 10 mol / L nitric acid solution, soaked at room temperature for 5 hours, taken out and immersed in a sufficient amount of 18 g / L tin chloride aqueous solution, soaked at room temperature for 3 hours, taken out and placed in a mixed solution, the mass volume ratio of the composite nanofibers to the mixed solution is controlled to be 1:50 g / mL, the mixed solution is composed of 0.18 g / mL glucose solution, 0.25 g / mL polyvinyl pyrrolidone solution, 20 wt% ammonia water and 30 g / L silver nitrate solution in a volume ratio of 4.5:1:3.2:4.6, transferred to a reactor, reacted at 130°C for 8 hours, taken out and repeatedly washed with distilled water and then dried.

[0067] A method for preparing aluminum conductive paste for solar cells, the specific operations are as follows:

[0068] The silver-doped composite nanofibers are pretreated, crushed and ground to obtain powder, which is dispersed in an organic additive together with a metal element compound, mixed, and then aluminum powder and inorganic powder are added and ground to obtain the aluminum conductive paste, wherein the fineness of the aluminum conductive paste is <20 μm and the viscosity is 40000 Pa.s.

[0069] The pretreatment of the silver-doped composite nanofibers is specifically performed as follows:

[0070] 1) Weigh 8.9 g of potassium antimony tartrate and dissolve it in 50 mL of deionized water, stir at 800 r / min for 30 min, and after it is fully dissolved, add 0.6 g of polyvinyl pyrrolidone and continue stirring for 20 min, then add 2.7 g of thioacetamide to the mixed solution and continue stirring for 40 min to obtain a reaction solution for standby use;

[0071] 2) Add silver-doped composite nanofibers to the reaction solution, control the ratio of the two to be 1:30 g / mL, then transfer to a reactor, seal it and place it in an oven, react at a constant temperature of 200°C for 5 hours, after the reaction is completed, cool to room temperature, take out the product, rinse it repeatedly with deionized water, and dry it.

[0072] Comparative Example 1: This comparative example is basically the same as Example 1, except that inorganic glass powder is used to replace the silver-doped composite nanofibers.

[0073] Comparative Example 2: This comparative example is basically the same as Example 1, except that silver nanoparticles are not used to modify the surface of the composite nanofibers.

[0074] Comparative Example 3: This comparative example is basically the same as Example 1, except that the silver-doped composite nanofibers are not pretreated.

[0075] Test Trial 1:

[0076] The aluminum conductive paste samples for solar cells provided in the above-mentioned embodiments 1-3 and comparative examples 1-3 were respectively tried out on the production line; the specification of the polycrystalline silicon wafer is: 156.75×156.75mm, the thickness before printing is 180μm, firstly, a 200-mesh screen is used to print the back silver electrode paste (DuPont PV505), and then it is dried, and then a 280-mesh screen is used to print the aluminum conductive paste sample for solar cells, the printing weight is 1.5 grams of paste per piece, the drying temperature is 125°C, the drying time is 4min, and then a 200-mesh screen is used to print the front silver electrode paste (DuPont 16C), and it is dried and sintered in a tunnel furnace, the temperature gradient distribution of the tunnel furnace, the time in the tunnel furnace is 2min, the sintering peak temperature is 890°C, and the time is 2s. After it comes out of the furnace, the performance of each battery cell is tested.

[0077] (1) Surface condition: Visually inspect the back surface condition. If it is smooth and free of aluminum beads or aluminum blisters, it is marked as OK. Otherwise, it is marked as NG.

[0078] (2) Adhesion: Soak each cell in tap water at room temperature for 7 days. If the back field metal film does not fall off or does not fall off when gently scraped with a blunt object, it is marked as OK; otherwise, it is marked as NG.

[0079] (3) Warpage: The degree of curvature of the cell was measured with a vernier caliper in mm. This was repeated 100 times and the average value of the warpage was recorded.

[0080] (4) Photoelectric conversion efficiency: A single flash simulator was used to test each cell according to the method disclosed in IEC904-1. The test conditions were standard test conditions (STC): light intensity: 1000 W / m2; spectrum: AM1.5; temperature: 25°C. The test was repeated 100 times and the average value of the photoelectric conversion efficiency was recorded.

[0081] The test results are shown in Table 1.

[0082] Table 1

[0083] Surface condition Adhesion Warpage mm Photoelectric conversion efficiency Example 1 OK OK 0.23 17.85% Example 2 OK OK 0.21 17.93% Example 3 OK OK 0.27 17.79% Comparative Example 1 OK OK 0.85 17.16% Comparative Example 2 OK NG 1.12 17.25% Comparative Example 3 OK NG 1.53 17.42%

[0084] It can be seen from the above test results that the aluminum conductive paste in the present invention, after being printed on a solar cell and sintered into a film, has a high photoelectric conversion efficiency and a small warping of the cell, thereby making the yield rate of the solar cell high.

[0085] Test Trial 2:

[0086] Based on the sample of Example 1, the influence of the content of silver-doped composite nanofibers in the aluminum conductive paste on the warpage of the battery cell was compared. Figure 1 ,pass Figure 1 It can be seen that with the increase of the content of silver-doped composite nanofibers, the warpage of the battery cell gradually decreases, but when the content of silver-doped composite nanofibers exceeds a certain value, the warpage of the battery cell shows an upward trend.

[0087] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An aluminum conductive paste for solar cells, characterized in that: The aluminum conductive paste comprises aluminum powder, silver-doped composite nanofibers, inorganic powder, organic additives, and metal element compounds; based on the total weight of the aluminum conductive paste, the content of the aluminum powder is 70-82wt%, the content of the composite nanofiber powder is 5-10wt%, the content of the inorganic powder is 1-3wt%, the content of the organic additive is 10-20wt%, and the content of the metal element compound is 0.1-0.6wt%; The preparation method of silver-doped composite nanofibers is as follows: 1) Dissolve an appropriate amount of polyacrylonitrile and polyvinyl pyrrolidone in N,N-dimethylformamide, stir for 3-5 hours, add zirconium n-propoxide and glacial acetic acid, mix well to form a spinning solution for electrospinning, pre-oxidize the obtained product in air for 1-3 hours, then keep it warm in a nitrogen atmosphere for 1-2 hours, and cool to room temperature to obtain composite nanofibers; 2) After the composite nanofibers are fully washed with anhydrous ethanol, they are immersed in a sufficient amount of nitric acid solution for 3-5 hours at room temperature. After being taken out, they are immersed in a sufficient amount of tin chloride aqueous solution for 1-3 hours at room temperature. After being taken out, they are placed in a mixed solution, transferred to a reactor, reacted at 120-130°C for 5-8 hours, and after being taken out, they are repeatedly washed with distilled water and dried; The mixed solution is composed of 0.12-0.18 g / mL glucose solution, 0.20-0.25 g / mL polyvinyl pyrrolidone solution, 15-20 wt % ammonia water and 20-30 g / L silver nitrate solution in a volume ratio of (3.6-4.5):1:(2.8-3.2):(4.0-4.6); The pretreatment of silver-doped composite nanofibers is specifically performed as follows: 1) Weigh an appropriate amount of potassium antimony tartrate and dissolve it in deionized water. Stir for 10-30 minutes. After it is fully dissolved, add polyvinyl pyrrolidone and continue to stir for 10-20 minutes. Then add thioacetamide to the mixed solution and continue to stir for 30-40 minutes to obtain a reaction solution for standby use; 2) Add the silver-doped composite nanofibers to the reaction solution, then transfer it to a reactor, seal it and place it in an oven for constant temperature reaction. After the reaction is completed, cool it to room temperature, take out the product, rinse it repeatedly with deionized water, and dry it.

2. The aluminum conductive paste for solar cells according to claim 1, characterized in that: The inorganic powder is at least one of zirconium tungstate and zirconium vanadate; The metal element compound is at least one of tetraethyltin, dibutyltin dilaurate, tetrabutyl lead and silver laurate; The organic auxiliary agent contains 5-12 wt % of a thickener, 1-5 wt % of a lubricant, 1-5 wt % of a thixotropic agent and 80-90 wt % of an organic solvent.

3. The aluminum conductive paste for solar cells according to claim 2, characterized in that: The organic solvent is selected from at least one of terpineol, turpentine, ethylene glycol ethyl ether acetate and tributyl citrate.

4. The aluminum conductive paste for solar cells according to claim 1, characterized in that: In step 1), in the spinning solution, the ratio of polyacrylonitrile, polyvinyl pyrrolidone, N,N-dimethylformamide, zirconium n-propoxide and glacial acetic acid is (3-6) g: (4-9) g: (60-100) mL: (7-13) mL: (3-5) mL; The electrospinning is carried out at a voltage of 11-15 kV and a spinning rate of 1.1-1.6 mL / h; The pre-oxidation temperature is 255-280°C; The insulation temperature is 1200-1300°C.

5. The aluminum conductive paste for solar cells according to claim 1, characterized in that: In step 2), the concentration of the nitric acid solution is 8-10 mol / L; The concentration of the tin chloride aqueous solution is 13-18 g / L; The mass volume ratio of the composite nanofiber to the mixed solution is 1: (30-50) g / mL.

6. The method for preparing the aluminum conductive paste for solar cells according to any one of claims 1 to 5, characterized in that: The specific operations are as follows: The silver-doped composite nanofibers are pretreated, crushed and ground to obtain powder, which is dispersed in an organic additive together with a metal element compound. After mixing, aluminum powder and inorganic powder are added and ground to obtain the aluminum conductive paste, wherein the fineness of the aluminum conductive paste is <20 μm and the viscosity is 30,000-40,000 Pa.s.

7. The method for preparing the aluminum conductive paste for solar cells according to claim 6, characterized in that: In step 1), in the reaction solution, the ratio of potassium antimony tartrate, deionized water, polyvinyl pyrrolidone, and thioacetamide is (7.2-8.9) g: (30-50) mL: (0.2-0.6) g: (2.3-2.7) g; The stirring speed is 500-800r / min.

8. The method for preparing the aluminum conductive paste for solar cells according to claim 7, characterized in that: In step 2), the ratio of the silver-doped composite nanofibers to the reaction solution is 1: (10-30) g / mL; The isothermal reaction temperature is 180-200° C., and the reaction time is 4-5 hours.

Citation Information

Patent Citations

  • Aluminum electrically conductive slurry used for solar cell and preparation method thereof

    CN103177791A

  • Aluminum back field slurry applied to solar battery, preparation method thereof, preparation method of solar battery piece and solar battery piece

    CN103426496A